Financial and Administrative Measures for the Development of Tourism after COVID-19 - AISIN, Marat Zh.; AITKAZINA, Madina; MAULINA, Nurgul Hasanovna; ZHAKIPBEKOV, Dinmukhamed Saparovich; SAPAROVA, Gulnara Telmanovna (Journal of Environmental Management and Tourism, 2022)
The recent decades demonstrate that tourism is one of the sectors that develop the most consistently and form the backbone of the economies of many developed and developing countries. In this context, one of the main problems hindering the promotion of tourism services is the relatively high probability of force majeure situations. Whereas forced flight cancellations, floods, or hurricanes are local events, the consequences of the COVID-19 pandemic have taken their toll on the entire tourism sector. Today, the tourism sector is one of the most affected by the COVID-19 pandemic. This may provoke further regression given the weak global economy, geopolitical, social, and trade tensions, and uneven performance among major outbound travel markets. At the same time, over many years, tourism has been consistently proving its resilience and ability not only to recover from economic crises but also to contribute to a broader economic and social recovery. The goal of the present study is to develop proposals for the introduction of financial and administrative measures for the development of the tourism industry in the post-pandemic period. Data for the study are collected by means of document analysis and an expert survey. The study concludes that in order to overcome the adverse economic effects of the COVID-19 pandemic in the sphere of tourism, a number of financial and administrative measures need to be developed and implemented at the level of state and local government institutions, particularly in Kazakhstan, to support the development of the tourism sector and stimulate the activities of tourism enterprise. For their part, the authors propose the key measures that should improve the financial sustainability and organization of the tourism sector in Kazakhstan .